1999
DOI: 10.25249/0375-7536.1999294497504
|View full text |Cite
|
Sign up to set email alerts
|

Relações Genéticas Entre Latossolos E Crostas Lateríticas Aluminosas E Alumino-Ferruginosas Na Região De Paragominas, Pará

Abstract: Structural, textural, mineralogical and chemical datas of two lateritic profiles located in Paragominas municipality, in the NE of Pará State, are studied. The profiles with three horizons: lower, intermediate and upper that correspond, respectively to massive lateritic crust, fragmented crust and soil, are formed by the weathering of the crust in wet climate with rain forest. In these conditions the lateritic crust form the top latosol by the lost of aluminiun and iron as consequence of the dissolution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
2
9
0
8
Order By: Relevance
“…The presence of clay horizons whose genesis can be attributed to the resilication of old bauxitic levels has been recognized in several deposits in Brazil (Boulangé and Carvalho, 1989;Lucas, 1997;Varajão et al, 1989Varajão et al, , 1990Horbe and Costa, 1999;Oliveira et al, 2013b). In the Amazon, for example, the clay layer on top of many deposits, such as Porto de Trombetas, Juruti, Rio Capim, and Paragominas, was described as homogeneous, without stratification, and eminently kaolinitic.…”
Section: Resilication Process and Its Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of clay horizons whose genesis can be attributed to the resilication of old bauxitic levels has been recognized in several deposits in Brazil (Boulangé and Carvalho, 1989;Lucas, 1997;Varajão et al, 1989Varajão et al, , 1990Horbe and Costa, 1999;Oliveira et al, 2013b). In the Amazon, for example, the clay layer on top of many deposits, such as Porto de Trombetas, Juruti, Rio Capim, and Paragominas, was described as homogeneous, without stratification, and eminently kaolinitic.…”
Section: Resilication Process and Its Indicatorsmentioning
confidence: 99%
“…Although resilication has been reported as a common process in the evolution of many bauxitic deposits, it has rarely been addressed as a soil-forming process. We highlight here the studies of Horbe and Costa (1999) that showed the genetic relation between Latosols and the lateritic crusts in the north of Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essas crostas retratam alternâncias de climas secos e úmidos atuantes na área durante o Pleistoceno e que, com o retorno de maior umidade, entram em desequilíbrio com o meio e sofrem degradação biofísica e bioquímica, o que resulta na geração de latossolos concrecionários (Tardy 1993). A transformação de crostas lateríticas em latossolos tem sido amplamente discutida no âmbito amazôni-co, e a atividade vegetal é apontada como um dos fatores importantes nesse processo (Horbe & Costa 1997, 1999, 2005. Os perfis lateríticos truncados ao nível do horizonte mosqueado contribuíram substancialmente com a formação in situ dos solos arenosos a areno-sílticos e, em conjunto, com a formação dos sedimentos das veredas As assinaturas mineraló-gicas e geoquímicas desses regolitos demonstram afinidades evolutivas entre eles.…”
Section: Elementos Traços E Terras Rarasunclassified
“…Nessas condições desenvolvem-se crostas lateríticas ferruginosas, bauxíticas, fosfáticas, niquelíferas e manganesíferas que constituem importantes jazidas minerais (Bardossy & Aleva 1990, Costa 1990, Costa 1997, Lucas 1997, Boulangé & Carvalho 1997, Horbe & Costa 1999, Kostchoubey et al 2005, Costa et al 2005, Silva et al 2012. As crostas são importantes marcadores morfo-estratigráficos e fornecem subsídios para correlação topográfica e evolutiva da paisagem (Tardy & Roquin 1998, Twidale & Bourne 1998.…”
Section: Introductionunclassified